Pan-Arab task force in Iraq : the case for regional intervention - Beaurpere, Guillaume N. (2015)
The security situation in Iraq remains tenuous despite recent tactical gains against the Islamic State. For both political and military reasons, Baghdad should agree to the deployment of a Pan-Arab task force to enforce peace in northern Iraq.